GEOMORFOLOGI DAN KARAKTERISTIK NIKEL LATERIT DI DESA BAINGKETE DISTRIK MAKBON KABUPATEN SORONG PROVINSI PAPUA BARAT - Meriana Harahap; Eka Novitasari (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2022)
Nickel deposits geologically came from weathering of abducted ultrabasic igneous rock. The rock is exposed during removal, followed by a geomorphological process that develops laterazation. Geologically the Makbon area is on the path of the Sorong horizontal fault field which has been active since the beginning of the Miocene. The dominant Sorong fault movement to the west exposed ocean floor rocks including blocks of ultrabasic rock. To determine the mineralization of nickel laterite in the Makbon area, this study combines mapping and surface geological observation methods with XRF analysis in the laboratory. The results of the study are known that the research area is composed of six land formations, namely the Makbon Fault Block Ridge, Baingkete Fault Block Ridge, Bancuh Baingkete Hills, Baingkete Bald Mountain Bancuh Hills, Makbon Fault Structure Denudation Plain, and Dore Bay Hills. Geomorphological control of the distribution of laterite nickel on steep slopes produces a thin, thickened laterite layer on the topography of the ramps. The characteristics of laterite nickel deposits in Baingkete Village are Type A deposits (Mg-Ni Silicate), on serpentinite bedrock, which consist of laterite profiles of limonite zone, saprolite zone, and bedrock zone